Peran Etika Dalam Membangun Profesionalisme Di Bidang Hukum - Muhammad Qodafi Al Pangkany; Faridatun Nisa; Rofi Risti Fauziawati; Tita Sirdan Maulana (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
This article identifies the key role of ethics in building professionalism in the legal field, including increasing public trust, preventing abuse of authority, and improving the quality of legal services. Through the application of ethical principles, legal professionals can demonstrate their commitment to integrity and fairness, which in turn strengthens public trust in the legal system. This article also explores challenges in implementing ethics, such as structural barriers, external pressures, and conflicts of interest. Building an ethical culture in the workplace and raising public awareness about the importance of ethics in legal services are also proposed as important steps. With this strategy, it is hoped that awareness and application of ethics among legal professionals can be increased, thereby strengthening the integrity and effectiveness of the legal system as a whole.